Genetic evidence supports Sylvilagus mansuetus (Lagomorpha: Leporidae) as a subspecies of S. bachmani - Álvarez-Castañeda, Sergio Ticul; Lorenzo, Consuelo (Zootaxa, 2016)
Since Sylvilagus bachmani (Lagomorpha: Leporidae) from the Baja California Peninsula and S. mansuetus from San Jose Island, Mexico, display an allopatric distribution and are closely related, their taxonomy is unclear. The phylogenetic relationships among specimens of both species were evaluated using two mitochondrial genes (Cyt b, COI) and the beta-fibrinogen nuclear gene intron 7 (β-fib I7). The genetic analyses revealed that S. mansuetus was included within the S. bachmani clade as the sister-group of S. b. cerrosensis. The genetic distances among S. b. cerrosensis and mansuetus were relatively low (1.3% with Cyt b), similar to intraspecific distances observed within other species of Sylvilagus. We consider mansuetus to be a subspecies of S. bachmani, and the morphological traits previously used to differentiate the two taxa should be used to distinguish S. b. mansuetus from the other subspecies of S. bachmani.